Принципи права в компаративістському контексті - Тихомиров, О.Д. (Альманах права, 2012)
У статті висвітлюються аспекти компаративістського підходу до осмислення принципів права. Обґрунтовується доцільність їх пізнання у «форматі» співвідношення загального, особливого, одиничного та унікального. В статье освещаются аспекты компаративистского подхода к осмыслению принципов права. Обосновивается целесообразность их познания в «формате» соотношения общего, особенного, единичного и уникального. Article is devoted to aspects of the comparative understanding of the principles of law in the «format» value for the general, special, single and unique, based on the recognition of pluralism and equality of legal cultures, the interaction of legal systems, the need to develop a global legal space not only universal but also regional, national original, which is aimed at more efficient use of the comparative approach and achievements of modern comparative law. The article notes that during the years of Ukraine’s independence, principles of law in a particular aspect investigated more than 180 theses on jurisprudence, which unlike traditional Soviet legal science, more attention is
drawn to their pluralism (diversity) not only in the context of the respective classifications, but the ratio of human, civilization and national values.The author emphasizes the basic approach to understanding the principles of comparative law is the knowledge of
their value because of the general, special, single and unique quality in the coordinates (properties) and quantitative (prevalence) measurements. Its feature as opposed to purely theoretical approach is that understanding the principles of law oriented towards the specific realities (legal acts, legal awareness, legal practice, legal research, etc.) to clarify common and different between them in the context of the selected range of objects mapping (world order, interstate and super-state association, national legal systems, their components, etc.), and in diachronic and synchronic
aspects, or, preferably, in their unity. The second feature is that it is not based on the universality of existence and knowledge of the principles of law, and their pluralism — diversity. The article emphasizes that the originality of comparative approach to the knowledge of the principles and appears to use the format «one — the second — other», which allows you to display, record, learn principles of law
in relations porivnyanosti — neporivnyanosti, and using the concept of relativity — depending on interpretation of legal principles of aspects of coordinates reason, parameters not only study, but the real processes of their genesis,
formation of prevalence. Yes, as a form of knowledge of the principles of law as diverse as our own principles of law that is uncertain possibility of a unified and true (theory, concept, doctrine) about them. The article notes that each of the existing forms of knowledge of the principles of law (philosophy, science, religion, mythology, and everyday practical knowledge) reflects and understands the world of her legal means,
methods, ways and forms as a result of the peculiar world view, which are regulators of conduct and their thinking. Real space transformation principles of law and their understanding of diversity and equality formed countries, cultures, civilizations, and consequently the principles of national law, which became official recognition at the
international and national levels. This allows, in the opinion of the author to distinguish among the principles of law principle komparatyvnosti rights as recognition of generality, features and uniqueness (originality) legal culture (national legal systems, traditions, etc.). The paper formulated the conclusion that vision Comparative principles of law aimed at understanding their formation, recognition and knowledge in the context of the general, special, single and unique formats of time, space, diversity of legal cultures, the reality of their interactions.